Quantification of Postoperative Posterior Malleolar Fragment Reduction Using 3-Dimensional Computed Tomography (Q3DCT) Determines Outcome in a Prospective Pilot Study of Patients With Rotational Type Ankle Fractures. Issue 8 (August 2019) - Meijer, Diederik T.; de Muinck Keizer, Robert-Jan O.; Stufkens, Sjoerd A. S.; Schepers, Tim; Sierevelt, Inger N.; Kerkhoffs, Gino M. M. J.; Goslings, J. Carel; Doornberg, Job N.
Abstract : Objective: To correlate Q3DCT measurements of residual step-off, gap, and 3D multidirectional displacement of postoperative posterior malleolar fracture fragment reduction in patients with rotational type ankle fractures, with patients' clinical outcome using standardized patient- and physician-based outcome measures. Design: Prospective cohort study. Setting: Level-I Trauma Center. Patients: Thirty-one patients with ankle fractures including a posterior malleolar fracture (OTA/AO type 44) were included. Intervention: All patients underwent open reduction internal fixation of their ankle fracture, of which 18 patients (58%) had direct fixation of the posterior malleolar fragment. Decision of (direct) fixation of the posterior malleolar fragment was not standardized and guided by surgeons' preference. Main Outcome Measurements: Quality of postoperative reduction was quantified using Q3DCT: posterior fragment size (% of joint surface), residual step-off (mm), postoperative gaps (mm 2 ), and overall multidirectional displacement were quantified. Foot and Ankle Outcome Score pain and symptoms subscales and quality of life (Short Form-36) at 1 year postoperatively were included as the main outcome measures. Results: Step-off (mean 0.6 mm, range 0.0–2.7, SD 0.8) showed a significant correlation with worse Foot and Ankle Outcome Score pain and symptoms subscales. Residual fracture gap (mean 12.6 mm 2, range 0.0–68.8, SD 19.5) and 3D multidirectional displacement (mean 0.96 mm, range 0.0–2.8, SD 0.8) showed no correlation. Conclusions: In patients with rotational type ankle fractures involving a posterior malleolar fracture, contemporary Q3DCT measurements of posterior fragment size and residual intra-articular step-off—but not gap—show significant correlation with patient-reported pain and symptoms. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.